Activité dialogique et micro-improvisations en entretien de conseil en orientation - Isabelle Olry-Louis (Activités)
We advocate the utility of considering the ordinary interactions of career counseling as an activity which needs to be analysed in reference to theories of the activity, to situated action and to conversational analysis. Our position may be summarized as follows: 1) counselling is always improvised to some extent (micro-improvisations); 2) this has to be the case, due to the properties of the situation, namely the asymmetry of the relationship between the consultant and the counsellor, the former being asked to provide the "materials" upon which the latter interactionally performs his/her professional acts; 3) so whilst they both have to improvise, they do so in different ways, because their respective uncertainties have different sources: the consultant never knows exactly what he/she is supposed to say in a given situation and the counsellor never knows what effects his/her interventions will have; 4) the success of a vocational counselling interview therefore depends on the degree of adjustment the partners will be able to reach in a joint process seen as a "dialogical improvisation". We will then focus on the vocational counselling activity as a joint process in which takes place during the course of situated interactions, with the objective of gaining a better understanding of the pragmatic processes involved in the monitoring of the interaction progress. Empirical data will be taken into account through the analysis of a certain number of excerpts from a corpus of interviews carried out by young vocational counsellors.